2020
DOI: 10.1016/j.omto.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 Accelerates the Growth of Human Liver Cancer Cells by Activating CDK2 via Targeting H3F3A

Abstract: miR-155 is associated with the promotion of tumorigenesis. Herein, we indicate that abnormal miR-155 was negatively correlated with the expression of P21WAF1/Cip1. Our results suggest that miR-155 alters the transcriptome and inhibits the expression of H3F3A in liver cancer cells. Therefore, miR-155 inhibits the methylation modification of histone H3 on the 27 th lysine. Notably, on the one hand, miR-155-dependent CTCF loops cause the CDK2 interacting with cyclin E in liver cancer cells; on the other hand, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“… 36 Long noncoding RNA DUXAP8 promotes pancreatic carcinoma progression via the miR‐448/WTAP/Fak signaling axis 37 and miR‐155 accelerates the growth of human liver cancer cells by activating CDK2 via targeting H3F3A . 38 In addition, miR‐200c targets CDK2 and suppresses tumorigenesis in RCC. 39 These results suggest that miRNA, WTAP , and CDK2 are jointly involved in the progression of various tumors, which is consistent with our experimental results showing that miR‐501‐3p enhances the progression of RCC via the miR‐501‐3p/WTAP/CDK2 axis.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Long noncoding RNA DUXAP8 promotes pancreatic carcinoma progression via the miR‐448/WTAP/Fak signaling axis 37 and miR‐155 accelerates the growth of human liver cancer cells by activating CDK2 via targeting H3F3A . 38 In addition, miR‐200c targets CDK2 and suppresses tumorigenesis in RCC. 39 These results suggest that miRNA, WTAP , and CDK2 are jointly involved in the progression of various tumors, which is consistent with our experimental results showing that miR‐501‐3p enhances the progression of RCC via the miR‐501‐3p/WTAP/CDK2 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, no further analyses were performed in this study to assess the impact of miR-155 in Hep3b aggressiveness. A recent study has demonstrated that miR-155 plays a pro-tumoral role in hepatocarcinogenesis through the inhibition of H3F3A expression and H3K27 methylation, which blocks the expression of the P21WAF1/CIP1 tumor suppressor gene [103]. Similarly, the downregulation of miR-122 has been found to be related to Sorafenib resistance in liver cancer cells [104].…”
Section: Non-coding Rnas Small Rnasmentioning
confidence: 98%
“…Other risk factors include chemical carcinogens exposure, obesity, diabetes, and alcohol abuse (Fig. 1C) [10][11][12][13], and the HCC incidence has been on the rise in recent years. Meanwhile, there are significant geographical differences in the risk factors for HCC, mirroring the variation in global distribution patterns.…”
Section: Current Epidemiology Of Hccmentioning
confidence: 99%